Corporate Governance and Cash Holdings among Non-Financial Companies Listed in the Nigerian Exchange Group - Agbonrha-Oghoye Imas Iyoha; Victor Chukwudeme Odu; Okuns Omokhudu (Jurnal Dinamika Akuntansi dan Bisnis)
The exogenous shocks that necessitate firm deviation from a target cash holding vary across firms and institutional environments, hence the need for the study. This study examines the relationship between corporate governance (CG) and cash holdings among non-financial companies in the Nigerian Exchange Group between 2011 and 2020. The number of populations is 133 non-financial firms. As not all firms disclosed publicly comprehensive annual reports  the number of final samples is 88 firms. Generalized Method of Moments (GMM) and the quantile techniques were adopted. With a speed of adjustment (SOA) of 0.75 and a time frame of one year, three months, and four days (1/0.749 = 1.34), the result reveals a partial dynamic adjustment to target cash holdings. The quantile estimation generally reveals low cash holdings and high SOA dynamics, and it is significant at 5% level. With exception of board gender diversity and institutional ownership, variables such as board independence, size, and chief executive officer equity ownership exhibit a significant inverse impact on cash holdings at a 5% level. Relying on the dynamic trade-off and agency theories, the results conform to a prior expectation. This study recommends that a manager should formulate strategic financial policy based on a firm’s specific SOA.